Filaggrin mutations are strongly associated with contact sensitization in individuals with dermatitis. (24th January 2013) - Thyssen, Jacob P.; Linneberg, Allan; Ross‐Hansen, Katrine; Carlsen, Berit C.; Meldgaard, Michael; Szecsi, Pal B.; Stender, Steen; Menné, Torkil; Johansen, Jeanne D.
Abstract : Background. Although heterozygous filaggrin gene ( FLG ) mutation carriers seem to have an increased risk of atopic, irritant and allergic nickel dermatitis, it remains unclear whether the risk of contact sensitization to allergens other than nickel is also elevated in FLG mutation carriers. Objectives. We hypothesized that heterozygous FLG mutation carriers who suffer from dermatitis will have strongly reduced or even absent filaggrin levels during episodes of inflammation, potentially increasing the penetration of contact allergens, and hence the risk of becoming sensitized. Materials and methods. During 2006–2008, 3335 randomly invited 18–69‐year‐old adult Danes participated in a general health examination, filled out a questionnaire, and were genotyped for the R501X and 2282del4 mutations in FLG . Results. A logistic regression analysis restricted to individuals who reported atopic dermatitis and frequent episodes of hand eczema showed a strong association between FLG mutations and contact sensitization to allergens other than nickel (odds ratio 5.71; 95% confidence interval 1.31–24.94). In participants without dermatitis, no association was found between contact sensitization and FLG mutations. Conclusion. FLG mutation carriers with self‐reported dermatitis have an increased risk of contact sensitization to substances other than nickel, whereas FLG mutations alone may not, or may only slightly, increase the risk of sensitization.